The Influence Of Brand Image Product Private Label, Service Quality, And Price Bundling On Customer Retention Through Customer Satisfaction At Indomaret Pontianak City - Muryati, Tri; Listiana, Erna (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to determine and provide empirical evidence regarding the influence of the brand image of private label products, service quality, and bundling prices on customer retention through customer satisfaction at Indomaret in Pontianak City. This research is a causal associative study with a quantitative approach. The population in this study consists of all customers of Indomaret in Pontianak City who have purchased private label products and bundling products. The sampling technique used was the purposive sampling method, which is a type of non-probability sampling, with a total of 100 respondents by collecting data through questionnaires. The data analysis method utilized was the results of the hypothesis tests which were statistically analyzed using the SPSS data processing program version 25. The results of the study indicate that the brand image of private label products significantly affects customer satisfaction, service quality significantly affects customer satisfaction, price bundling significantly affects customer satisfaction, the brand image of private label products does not significantly affect customer retention, service quality does not significantly affect customer retention, price bundling does not significantly affect customer retention, and customer satisfaction significantly affects customer retention.